Effect of different Levels of Fertilizer (DAP) onthe Publican (Calotropis procera) Leaves Content of Phenol and (N, P, K) Compounds (Damascus University Journal of agriculture sciences, 2021)
The experiment  was carried out in the Republic of Iraq in the capital Baghdad and in the Dora district to study the effect of different levels of fertilizer (DAP) on plant leaves content of  (Calotropis procera) in terms of phenolic compounds, as well as N, P and K, in pots where the soil used was sandy silt collected from the shoulder of the Tigris River, which contained 750g/ kg sand, 200 g/kg silt and 50 g/ kg   clay,  and the average virtual soil density was 1.1 Mega grams m-³. The average electrical conductivity (ECe) was 1.8 ds m-1, the soil pH was 7.2, the concentration of available nitrogen 20 mg kg-1 , 15 mg kg-1 phosphorus and 145 mg kg-1 potassium. Four levels of DAP fertilizer   (18:46 N: P) (100, 200, 300 and, 400 kg  ha-1) were applied to the publican seedlings of one year. The experiment was laid out according to completely randomized design (CRD) in three replications. Results showed that all the studied traits were significantly higher at the fertilization of 400 kg DAP  per ha compared with the other levels. There was a significant  increase in the content of phenolic compounds, especially Epicatechin (48.72, 87.20, 137.18%) at the three higher levels of DAP compared to the first level (100 kg ha-1). The percentage increase in the content of p- coumaric was 43.82, 85.39 and 92.13%  to the level of the second, third and fourth respectively compared to the first level.  The Ferulic acid, Queretin - 3β-D-glycoside, Rutin and chlorophyll contents were the highest at the fourth level of 400 kg DAP ha-1 with a the percentage increase of 1050, 86, 164.81 and 40.47% respectively compared to the first level. There was a significant increase in the Nitrogen, Phosphorus and Potassium content (80.99 and 155.00 and 65.38% respectively) at the higher three levels compared to the first one.
Keywords: DAP; Phenolic compounds; Calotropis procera.